The 2017 French Presidential Elections A Political Reformation? - Evans, Jocelyn (French Politics, Society and Culture, 2018)
Emmanuel Macron's victory in the 2017 presidential elections represents one of the most important disruptions to French political life since the establishment of the Fifth Republic. This book analyses the political opportunities enabling a neophyte to conquer the Elysée, and the conditions leading to the unprecedented presidential runoff between this centrist EU enthusiast and pro-globalization candidate and the nationalistic/populist alternative embodied by Marine Le Pen. The book begins by considering trends in party competition and presidentialism in modern France, notably presidential primaries and their impact on party competition. It then moves to considering the role traditional explanatory factors in elections, namely policies and voter profiles, played in the result. Finally, it examines the dynamics of President Macron's success in the legislatives, and how he dominated the traditional party blocs. This book will appeal to students of French politics as well as those interested in electoral behaviour and European political systems.